Social Media Integration in SMEs: A Study on Business Performance Enhancement in Indonesia - Sukma, Andhi; Kaniawati, Keni; Oktaviani, Desy (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The background of this article emphasizes the significance of social media adoption and innovation for small and medium-sized enterprises (SMEs) in Indonesia, with a view to enhancing business performance in the context of technological and competitive challenges. This study explores what web-based entertainment reception and innovation similarity mean for presenting little and medium-sized endeavors (SMEs) in Indonesia. It analyzes how SMEs utilize virtual entertainment to support business execution amid mechanical difficulties and rivalry. Information was gathered from 450 SMEs across four help enterprises — cafés and inns, medical care, discount and retail, and schooling — using an online overview led through Google Structures from December 2023 to February 2024. The information was examined utilizing halfway least squares primary condition displaying (PLS-SEM) to investigate the connections between web-based entertainment reception, innovation similarity, and SME execution. Results show a critical positive connection between virtual entertainment reception, innovation similarity, and SME execution. SMEs that integrate online entertainment into their procedures show improved brand permeability, client commitment, and execution. The study suggests that Indonesian SMEs can gain a competitive edge by adopting social media platforms. Investing in technology training and infrastructure is recommended for seamless social media integration. Encouraging innovation and digital literacy among employees can further enhance SME success in the digital age. This exploration adds to the writing by showing the advantages of virtual entertainment reception on SME execution in Indonesia. It offers functional experiences for SME proprietors and supervisors to utilize web-based entertainment decisively for business development and maintainability.